2022
DOI: 10.1002/pat.5959
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously improving the hydrophobic property and flame retardancy of aluminum hypophosphite using rare earth based coupling agent for epoxy composites

Abstract: A novel hydrophobic rare earth‐based aluminum hypophosphite (AHP) was prepared using rare earth aluminate coupling agent (REA) in a ball mill with a one‐step mechanochemistry method, and used as flame retardant for epoxy resin. It has been found that RaAHP‐4 (AHP was modified by 4 wt% REA) exhibited excellent hydrophobic properties with the water contact angle of 94.58°. The effect of RaAHP‐2 (AHP was modified by 2 wt% REA) and RaAHP‐4 on the flame retardancy, thermal stability, and hydrophobic properties of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Another important application of ball milling is achieving the surface modification and functionalization of flame retardants for various purposes. For example, to enhance the hydrophobic property of aluminum hypophosphite, a rare earth-based coupling agent (REA) was utilized to modify the aluminum hypophosphite (AHP) through one-step ball milling [ 106 ], as shown in Figure 7 . This revealed that the AHP modified by 4 wt% REA (RaAHP-4) had an outstanding hydrophobic performance, with a water contact angle of 94.6.…”
Section: Ball Milling-assisted Fabrication Of Flame Retardantsmentioning
confidence: 99%
“…Another important application of ball milling is achieving the surface modification and functionalization of flame retardants for various purposes. For example, to enhance the hydrophobic property of aluminum hypophosphite, a rare earth-based coupling agent (REA) was utilized to modify the aluminum hypophosphite (AHP) through one-step ball milling [ 106 ], as shown in Figure 7 . This revealed that the AHP modified by 4 wt% REA (RaAHP-4) had an outstanding hydrophobic performance, with a water contact angle of 94.6.…”
Section: Ball Milling-assisted Fabrication Of Flame Retardantsmentioning
confidence: 99%